Upaya Guru Dalam Meningkatkan Kemampuan Anakmenghafal Surah Pendek Al-Qur’an Di Taman Kakan-Kanak - Latiefa Nisa Marsal (Jurnal Family Education, 2021)
This study aims to determine the teacher's efforts in improving the ability of children to memorize short letters of the Qur'an at Taman Kanak-kanak Ruhama’. Observations and interviews, as well as documentation were used for the data collection process in this study. The results of the study describe the teacher's efforts in improving the ability of children to memorize short letters of the Qur'an in Taman Kanak-kanak Ruhama Kelurahan Cupak Tangah Kecamatan Pauh, namely: (1) the efforts made by the teacher are doing muraja 'ah activities regularly, having a target memorization, using the right method, namely talqin, motivating children, directing and justifying children's reading and collaborating with parents. (2) the supporting factors faced in improving the ability of children to memorize short letters of the Qur'an are that children have enthusiasm, there is motivation that children can get from the school and parents, activities are carried out together and children are always present to school. And the inhibiting factors include children's lack of focus, unstable children's health and feelings, children often not attending because they often forget, and lack of support from parents.